The Impact of Mobile Service Quality, Perceived Value, Perceived Usefulness, Perceived Ease of Use, Customer Satisfaction Towards Continuance Intention to Use MyTelkomsel App - Azzahra, Talitha Radhiyya; Kusumawati, Nurrani (Integrasi Sains Media, 2023)
The community's high level of mobility has sped up mobile application development. Businesses from various industries raced to create their applications because it boosts brand loyalty and customer relationship, increasing revenue for the company. As the fifth-largest nation with a mobile application market share in 2021, Indonesia represents a sizable potential market in the next years. Telkomsel has capitalized on this potential by creating its mobile purchasing app, MyTelkomsel. The app has received 100 million downloads on Google Play Store and a 4.5-star rating. However, given that MyTelkomsel had a decline in monthly active users (MAU), falling to the 28th position in 2023, it is unclear whether it can keep its customers' intention to continue using the service. This study analyzes the conceptual model created by earlier related literature and identifies the factors that have a major impact on consumers' intentions to continue using MyTelkomsel. Customers of MyTelkomsel are the subjects of qualitative semi-structured interviews and quantitative surveys as part of this study. The interview findings were examined using open coding, while the questionnaire results were analyzed using PLS-SEM. According to the findings, Perceived Value, Perceived Usefulness, Perceived Ease of Use, and Customer Satisfaction positively impact Continuance Intention to Use. Service Content Quality and Customer Service Quality positively impact perceived Value and Customer Satisfaction. However, it has been demonstrated that Mobile Network Quality has no appreciable impact on Perceived Value. These results should help inform the development of stronger strategies for mobile app retention in the telecommunications sector or other relevant businesses in Indonesia. Future research is anticipated to include more factors, samples, and a wider scope due to research limitations better to explain the continual use intention of telecommunication apps.